Factors Used for Caries Prediction in First Infancy - Lívia Azeredo Alves ANTUNES; Leonardo dos Santos ANTUNES; Maria da Encarnação Perez Requejo da COSTA (Association of Support to Oral Health Research (APESB), 2006)
Objective: To evaluate the early presence of caries cavitation and active white spots (AWS) in maxilary anterior teeth in the primary dentition associating them with other factors (diet, fluor exposure, precocious ocorrence of mutans streptococci, oral hygiene) with the purpose of predict future caries lesion in posterior primary teeth. Method: The examination of the charts was done by the evaluation including anamnesis and clinical examination recorder in 250 files (young children with 18 - 36 months) attended at the Pediatric Dentistry Clinic from a public University Dental School of Rio de Janeiro in 2000 - 2003. Results: After data analysis, the result agree with other studies: the early experience of caries in anterior primary teeth was the best predictor of caries cavitation in deciduos molares (74,49%), other risks factors also have been significance in the prediction. After carie, the second most important variable was anterior teeth with white spots (58,82%), followed by high consuption of sugar (54%) and natural breastfeeding after 12 months of age (49,59%). Conclusion: This way this study could establish that dental caries is the best predictor, so preventive operatives shoud be done in early primary dentition.